Study of line-TFET analog performance comparing with other TFET and MOSFET architectures - Agopian, Paula Ghedini Der [UNESP]; Martino, João Antonio; Vandooren, Anne; Rooyackers, Rita; Simoen, Eddy; Thean, Aaron; Claeys, Cor (Elsevier, 2017)
In this work the Line-TFET performance is compared with MOSFET and Point-TFET devices, with different architectures (FinFET and GAA:Gate-All-Around) at both room and high temperatures. This analysis is based on the experimental basic analog parameters such as transconductance (gm), output conductance (gD) and intrinsic voltage gain (AV). Although the Line-TFETs present worse AV than the point-TFETs, when they are compared with MOSFET technology, the line-TFET shows a much better intrinsic voltage gain than both MOSFET architectures (FinFET and GAA). Besides the AV, the highest on-state current was obtained for Line-TFETs when compared with other two TFET architectures, which leads to a good compromise for analog application.
Keywords: Different device architectures; Intrinsic voltage gain; Line-TFET